Acquired hemophilia A (AHA): underreported, underdiagnosed, undertreated medical condition - Doaa M. El Demerdash; Alia Ayad; Noha Tawfik (SpringerOpen, 2022)
Abstract Background Acquired hemophilia A (AHA) is a rare acquired bleeding disorder occurred due to the formation of inhibitory antibodies neutralizing endogenous factor VIII. Main body About half the cases are idiopathic. Symptoms include severe and unexpected bleeding that could be life-threatening. High index of suspicion should be raised when unexplained subcutaneous or post-surgical bleeding with isolated prolonged APTT. Conclusions Acquired hemophilia A is a rare underdiagnosed underreported acquired hemostatic disorder that presents with sudden usually life-threatening bleeding; it is crucial to raise awareness and suspicion index of clinicians for early diagnosis and treatment to avoid morbidity and mortality.